Penyuluhan Dan Demplot Padi Beras Hitam di Desa Selat Kecamatan Narmada Lombok Barat - IGP Muliarta Aryana; I Wayan Sudika; AAK Sudhramawan; Ni Wayan Sri Suliartini; Dwi Ratna Anugrawati (Universitas Mataram, 2022)
The new superior variety Inpari Unram 1 BSP is functional rice because the rice is black and beneficial for health. This variety needs to be introduced to the Patuh Karya farmer group. This introduction was carried out in an effort to empower farmer groups as implementers of correct and integrated cultivation technology. This is done so that West Nusa Tenggara can maintain its position as a national rice barn and maintain rice self-sufficiency nationally. The problem encountered in the Patuh Karya farmer group in Selat village, Narmada District, West Lombok Regency is that they are not familiar with this new superior variety, both regarding the description of the variety, benefits and cultivation technology. The purpose of this activity is to introduce black rice about the description, content, benefits, and cultivation technology to farmers through counseling and plot demonstrations. The method used is lecture method, discussion and field practice in the form of demonstration plots (Demonstration plots). The implementation time starts from June to September 2022. The demonstration plot is held in paddy fields belonging to the Patuh Karya farmer group in Montong Daya Hamlet, Selat Village, Narmada District, West Lombok. The results of the activity showed that members of the Patuh Karya farming group, Montong Daya hamlet, Selat village, Narmada sub-district, West Lombok, understood the description of black rice rice of the Inpari Unram 1 BSP variety, the content and benefits of black rice for health, and understood black rice cultivation technology with the Jajar pattern. Legowo 4:1 as a result of counseling. Farmers are able to practice cultivating black rice of the Inpari Unram 1 BSP variety starting from soaking seeds, seeding, planting to harvesting, through demonstration plot activities and mentoring. Farmers will plant black rice in the following season and it is hoped that the team will seek market opportunities for black rice.